Incidence rate of anxiety and personality disorders and their interrelationship in senior-year students of the medical university - I. I. Ukraintsev; E. D. Schastnyy; N. A. Bokhan (Бюллетень сибирской медицины, 2020)
Objective: to study the incidence rate of personality and anxiety disorders and their interrelationship in seniors of the medical university.Materials and methods. The screening study for detection of personality and anxiety disorders using the Generalized Anxiety Disorder-7 (GAD-7) and Standardized Assessment of Personality – Abbreviated Scale (SAPAS) scales included 104 senior-year students of the medical university. In the studied sample, males (n = 46; 44.2%) and females (n = 58; 55.8%) (p < 0.05) were equally represented, the average age of men was 23 (23; 25) years, women – 23 (23; 23) years. Statistical processing was performed using the Pearson’s χ2 test, Mann–Whitney U test to compare independent samples, and the Spearman correlation analysis (r) with a preliminary estimate of the normal distribution.Results. The data on the statistically significant differences in the level of anxiety and personality disorders depending on gender and age were obtained. Using the GAD-7 scale, the presence of moderate and average level of anxiety in male students was revealed in 26.1%, in female students – in 48.3% (ð = 0.001). The use of SAPAS scale revealed statistically insignificant differences in the studied groups: in males – 4 (4; 6) points, in the group of female students – 4 (3; 5) points (ð = 0.2).Conclusion. A logistic regression model was obtained that predicted the highest likelihood of development of anxiety disorders.